Enhancing the Quality of Chicken Meatball with Egg Albumen as Binding Agent: Study on Chemical, Texture Profile, and Sensory Properties - Ismiarti Ismiarti; Abdul Rokhman; Muhamad Solkhan; Sugiyono Sugiyono; Teguh Dwi Putra (Politeknik Pembangunan Pertanian Manokwari, 2024)
Meatball is well-known meat product especially in Indonesia, made from various kind of meat that could be accepted by consumers. The study aimed to investigate chemical, texture profile, and sensory properties of broiler chicken meatball added by egg albumen as a natural additive to increase texture and sensory properties. Meatball composition consisted of chicken breast (60.12%), tapioca starch (20.04%), salt (2.51%), seasonings (2.3%), ice cube (15.03%) and egg albumen based on meat weights. The experiment study used Completely Randomized Design (CRD) with 5 treatments and 4 replications. Treatments consisted of the addition of 0% (P0), 5% (P1), 10% (P2), 15% (P3), and 20% (P4) egg albumen measured by meat proportion. Parameters assessed were chemical (protein and fat), textural profile (hardness, cohesiveness, springiness, and adhesiveness), and sensorial properties (color, taste, texture, and chewiness). Collected data of protein, fat, and texture profile were tested by analysis of variance, significant data continued by DMRT (Duncan’s Multiple Range Test). Sensory properties were analyzed by Kruskal Wallis. In result, the addition of egg albumen were significantly affected (p<0.05) to protein, fat, hardness, and all sensory properties, but it was not significantly affected (p>0.05) to cohesiveness, springiness, and adhesiveness. The addition of 20% egg albumen produced the highest protein and fat content, 11,83±0,30 and 1,55±0,17%, respectively. Then, hardness of chicken meatball on control treatment was the lowest than all treatment, with the highest was 2351,04±7,39 g. Average of cohesiveness, springiness, and adhesiveness were 0,66±0,02; 9,03±0,16 mm; and 0,04±0,03 mJ, respectively. The best sensory properties of chicken meatball with 20% egg albumen were white grayish color, delicious in taste, compact texture, and good chewiness. It could be summarized that adding 20% of egg albumen made the best characteristic on chemical dan sensory properties of chicken meatball.